Scaling up experiential learning tools for sustainable water governance in India (2020-2023) - International Food Policy Research Institute (2023)
IFPRI, ICRISAT, FES, and MLU-Halle. 2023. Scaling up experiential learning tools for sustainable water governance in India (2020-2023). PowerPoint presentation given during the FIA 2023.